(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2014)
Background: The objective of this study was to analyze the functional improvement of renal function in terms of split renal function (SRF) & glomerular filtration rate (GFR) by DTPA renogram in early post operative period who underwent A-H pyeloplasty for unilateral hydronephrosis due to congenital pelvi ureteric junction obstruction. Methods: A prospective observational study was conducted to see the post operative renal function improvement in patient with unilateral hydronephrosis due to congenital pelvi ureteric junction obstruction in department of paediatric surgery, BSMMU from July 2007 to October 2008. All the patients were followed up at 4 weeks interval for 12 weeks. Results: Total 13 Patients both male & female were observed with age ranging from 03 months to 15 years. Out of 13, eleven patients showed gradual improvement of renal function in terms of SRF & GFR in three successive DTPA renogram done at 4, 8 & 12 weeks post operatively but two patients showed deterioration of renal function in 1st two renogram but improved at 12th weeks period. Conclusion: DTPA renogram is the best method to see the functional improvement of renal function after A-H pyeloplasty but should be done on 12th post operative day. DOI: http://dx.doi.org/10.3329/jpsb.v2i2.19543